Everybody's gotta learn sometime - Planet Pop X Films; Saba Islamic Media ([S.l.] : Planet Pop X Films ; Kuala Lumpur : Saba Islamic Media (distributor))
Outlining the disturbing and heavily censored facts associated with the worst terrorist attacks in American history. While a grassroots movement worldwide continues to grow, and demand answers to the many unanswered questions, the public outcry for accountability and transparency
Title from title screen
Keywords: September 11 Terrorist Attacks, 2001; Terrorism -- United States